Synergistic effects of two naturally occurring iridoids in eliciting a rapid antidepressant action by up‐regulating hippocampal PACAP signalling. (22nd April 2022) - Zhang, Hailou; Sun, Yan; Yau, Suk‐yu; Zhou, Yanmeng; Song, Xinxin; Zhang, Han‐Ting; Zhu, Boran; Wu, Haoxin; Chen, Gang
Abstract : Background and Purpose: Current mainstream antidepressants have limited efficacy with a delayed onset of action. Yueju, a herbal medicine, has a rapid antidepressant action. Identification of the active ingredients in Yueju and the mechanism/s involved was carried out. Experimental Approach: Key molecule/s and compounds involved in this antidepressant action was identified by transcriptomic and HPLC analysis, respectively. Antidepressant effects were evaluated using various behavioural experiments. The signalling involved was assessed using site‐directed pharmacological intervention or optogenetic manipulation. Key Results: Transcriptomic analysis showed that Yueju up‐regulated pituitary adenylate cyclase activating polypeptide (PACAP) expression in the hippocampus. Two iridoids, geniposide and shanzhiside methyl ester, were identified and quantified from Yueju. Only co‐treatment with both, at an equivalent concentrations found in Yueju, increased PACAP expression and elicited a rapid antidepressant action, which were blocked by intra‐dentate gyrus infusion of a PACAP antagonist or optogenetic inactivation of PACAP expressing neurons. Geniposide and shanzhiside methyl ester co‐treatment rapidly inhibited CaMKII phosphorylation and enhanced mTOR/4EBP1/P70S6k/BDNF ignalling, while intra‐dentate gyrus infusions of a CaMKII activator blunted the rapid antidepressant action and BDNF expression up‐regulation induced by the co‐treatment. A single co‐treatment of them rapidly improved depression‐like behaviours and up‐regulated hippocampal PACAP signalling in the repeated corticosterone‐induced depression model, further confirming the involvement of PACAP. Conclusion and Implications: Geniposide and shanzhiside methyl ester co‐treatment had a synergistic rapid onset antidepressant action by triggering hippocampal PACAP activity and associated CaMKII–BDNF signalling. This mechanism could be targeted for development of fast onset antidepressants. Abstract :